Online Control and Optimization of Directional Drilling - unknown (2020)
Directional Steering System (DSS) has been established for well drilling in the oilfield in order to accomplish high reservoir productivity and to improve accessibility of oil reservoirs in complex locations. In this thesis, dynamic modeling of two different DSS were developed and optimized using different control and optimization techniques. Firstly, the Rotary Steerable System (RSS) which is the current state of the art of directional steering systems. In this work, we address the problem of real time control of autonomous RSS with unknown formation friction and rock strength. The work presents an online control scheme for real time optimization of drilling parameters to maximize rate of penetration and minimize the deviation from the planned well bore trajectory, stick-slip oscillations, and bit wear. Nonlinear model for the drilling operation was developed using energy balance equation, where rock specific energy is used to calculate the minimum power required for a given rate of penetration. A proposed mass spring system was used to represent the phenomena of stick-slip oscillation. The bit wear is mathematically represented using Bourgoyne model. Secondly, the autonomous quad-rotor DSS which has 4 downhole motors, is considered. In this work, a novel feedback linearization controller to cancel the nonlinear dynamics of a DSS is proposed. The proposed controller design problem is formulated as an optimization problem for optimal settings of the controller feedback gains. Gravitational Search Algorithm (GSA) is developed to search for optimal settings of the proposed controller. The objective function considered is to minimize the tracking error and drilling efforts. Detailed mathematical formulation and computer simulation were used for evaluation of the performance of the proposed techniques for both systems, based on real well data.